Strategi Penerapan Qanun No. 6 Tahun 2014 tentang Hukum Jinayah di Aceh - Dicky Armanda; Yusrizal Hasbi; Romi Asmara (Sekolah Tinggi Ilmu Administrasi Nasional, 2021)
This study aims to identify the strategy of implementing Qanun (law) No. 6/2014 on Jinayah (the act of sin) law in the Aceh province, Indonesia. The challenges of implementing the Qanun were also investigated during the study. This investigation was conducted in Lhokseumawe (a city in the Aceh province) and is believed as the area where more violations of shari'a (Islamic canonical law) occurred. The research method adopted was qualitative and the data were collected through interviews and document analysis. The results of the study reported that there are still some personalities or local Acehnese opposed to the implementation of the Jinayat law qanun. Most communities were also lack understanding of this qanun implementation. The findings of the study imply that the communication strategy that has been carried out between stakeholders has not yet reaped maximum results. It infers that the implementation of Qanun No. 6/2014 on Jinayah law has not been going well in Lhokseumawe City due to several motives. One of them is a lack of communication between stakeholders. Besides, unfairness occurred in prosecute violators of Qanun number 2014 concerning the Jinayah law. This means that this law is only applied to ordinary people and not the families of government officials or the rich. Besides, the Qanun Jinayah also believed discriminated against women, especially the victims of rape. In this case, the Qanun Jinayah proffers a double strain on the victims where women victims of rape must present evidence and witnesses.